Endovascular coiling vs. surgical clipping for ruptured intracranial aneurysms: an in-hospital outcome win ratio analysis from a Colombian tertiary center - Quiceno-Ramírez, Santiago; García-Pretelt, Enrique Carlos; Mejía-Quiñones, Valentina; Folleco-Pazmiño, Edgar (Frontiers in Radiology, 2025)
BackgroundThe optimal management approach for ruptured intracranial aneurysms remains debated, with limited real-world evidence from Latin American populations. This study compared in-hospital outcomes between endovascular coiling and surgical clipping using a hierarchical win ratio (WR) analysis.MethodsWe conducted a single-center retrospective cohort study of 194 patients with ruptured intracranial aneurysms treated at a tertiary referral center (2011–2022). Patients were treated with either endovascular coiling (n = 73) or surgical clipping (n = 121). The primary outcome was the win ratio, analyzing a hierarchical composite endpoint of: (1) in-hospital mortality, (2) unfavorable functional outcome at discharge (modified Rankin Scale >2), (3) major complications, and (4) prolonged ICU stay (>10 days). Secondary analyses included multivariable logistic regression and prespecified subgroup analyses by clinical severity and aneurysm location.ResultsBaseline measured characteristics were balanced between groups. The win ratio significantly favored endovascular coiling (WR 1.75, 95% CI: 1.67–1.84, p < 0.001), indicating 75% more wins in the hierarchical outcome comparison. All individual components significantly favored coiling: mortality (WR = 1.35, p < 0.001), unfavorable functional outcome (WR = 1.53, p < 0.001), major complications (WR = 1.70, p < 0.001), and prolonged ICU stay (WR = 1.25, p < 0.001). Benefits were consistent across subgroups, including Hunt & Hess grades I-II (WR = 2.00) and III-V (WR = 1.96), and across most aneurysm locations. In contrast, multivariate logistic regression for poor outcome showed a favorable but non-significant trend for coiling (OR = 0.55, p = 0.102), while confirming Hunt & Hess ≥3 (OR = 5.54, p < 0.001) and modified Fisher ≥3 (OR = 3.85, p = 0.044) as dominant prognostic factors.ConclusionIn this Colombian cohort, hierarchical outcome analysis suggested superior in-hospital outcomes for endovascular coiling vs. surgical clipping. However, the substantial attenuation of this association in adjusted analyses indicates that these apparent advantages may largely reflect case selection patterns rather than inherent treatment superiority, as residual confounding by aneurysm complexity cannot be excluded.